Two new species and new records of subfamily Trypetinae (Diptera: Tephritidae) from India - Singh, Maneesh Pal; Hancock, David Lawrence (Zootaxa, 2026)
Two new species of subfamily Trypetinae, viz. Acidoxantha paratotoflava Maneesh & Hancock, sp. nov. and Hemilea suneriae Maneesh & Hancock, sp. nov., are described from Himachal Pradesh, India along with keys to Indian species. Genus Rhagoletis Loew is recorded for the first time from India, from a species that is near to R. freidbergi Korneyev & Korneyev but not named yet due to a lack of sufficient material. The male of Euphranta nigripeda (Bezzi) is recorded for the first time.